2002
DOI: 10.1029/2002gl015080
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical production of nitrous acid on glass sample manifold surface

Abstract: [1] Significant production of HONO was observed on glass sample manifold wall surface when exposed to sunlight during the PROPHET 2000 summer measurement intensive. It is hypothesized that the artifact HONO was produced by photolysis of adsorbed nitric acid/nitrate on the manifold wall surfaces followed by the subsequent reaction of produced NO 2 and adsorbed H 2 O on surface. This observation suggests against the use of an unshielded glass manifold as a sampling inlet for the measurement of atmospheric HONO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 23 publications
5
134
3
Order By: Relevance
“…It is also well known that N 2 O 5 is taken up on surfaces and hydrolyzed (54). Due to such uptake, there is a reservoir of strongly adsorbed reactive oxides of nitrogen on surfaces in both environmental chambers (14) and in the field (13).…”
Section: Nomentioning
confidence: 99%
“…It is also well known that N 2 O 5 is taken up on surfaces and hydrolyzed (54). Due to such uptake, there is a reservoir of strongly adsorbed reactive oxides of nitrogen on surfaces in both environmental chambers (14) and in the field (13).…”
Section: Nomentioning
confidence: 99%
“…Thus, the mechanism proposed in the present study might explain a significant fraction of the observed HONO formation in the urban atmosphere, besides other postulated photolytic HONO sources. 38,47,49,[52][53][54] However, this estimate needs to be verified using data from further experiments performed under atmospheric conditions, and also investigations on the wavelength dependencies of the photolysis processes.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…As recent measurements of the photolysis of adsorbed HNO 3 (Zhu et al, 2010) found NO 2 * as the main photolysis product, Zhou et al (2011) assume that HONO formation by HNO 3 photolysis also follows the mechanism of NO 2 conversion provided by and Stemmler et al (2006). Adsorbed HNO 3 therefore acts as a reservoir or a source of NO x in rural environments (Zhou et al, 2002b(Zhou et al, , 2011. One might speculate if the reaction of NO 2 * formed by HNO 3 photolysis at the surface with adsorbed water is also enhanced with regard to the gas phase Reaction (R8), and thus can act as source of HONO from HNO 3 photolysis.…”
Section: Important Ground Sourcesmentioning
confidence: 99%